2018
DOI: 10.14202/vetworld.2018.1109-1119
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and immunological characterization of Hyalomma dromedarii and Hyalomma excavatum (Acari: Ixodidae) vectors of Q fever in camels

Abstract: Background and Aim:Q fever Coxiella burnetii is a worldwide zoonotic disease, and C. burnetii was detected in mammals and ticks. Ticks play an important role in the spread of C. burnetii in the environment. Therefore, the aims of this study were to detect Q fever C. burnetii in camels and ixodid ticks by molecular tools and identification of Hyalomma dromedarii and Hyalomma excavatum using molecular and immunological assays.Materials and Methods:A total of 113 blood samples from camels and 190 adult ticks were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 65 publications
6
42
0
Order By: Relevance
“…The low infection rate of C. burnetii in Hyalomma tick species reported in the present study is comparable with that reported elsewhere for Hyalomma ticks [53,73]. Most of the positives were detected in H. dromedarii and only one in a H. truncatum tick (1.1%).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The low infection rate of C. burnetii in Hyalomma tick species reported in the present study is comparable with that reported elsewhere for Hyalomma ticks [53,73]. Most of the positives were detected in H. dromedarii and only one in a H. truncatum tick (1.1%).…”
Section: Discussionsupporting
confidence: 89%
“…Combining several mitochondrial markers (12S, 16S and cox1), we were able to identify several species of Hyalomma ticks. The use of these markers has been increasingly useful for tick identification in several studies [51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, human Q-fever seropositivity was weakly correlated with goats. This is in contrast to previous studies [23, 55, 60], but in line with recent outbreaks in Canada, Australia and Netherlands [18, 61, 62].…”
Section: Discussionsupporting
confidence: 82%
“…For centuries, camels have played a significant role as a major human companion and a key contributor to the livelihood of mankind. Despite the known role of camels in zoonosis, many aspects of their health have not been studied before the emergence of the Middle East respiratory syndrome-coronavirus (MERS-CoV) in 2012 [1][2][3][4]. In fact, the possibility of spreading known and unknown zoonotic pathogens from camels to humans or other animals represents major public health and economic concerns [4][5][6].…”
Section: Introductionmentioning
confidence: 99%